Pressure to improve scores in standardized English examinations and their effects on classroom practices. - Zakaria, Noor AsmaIffah; Abd. Samad, Arshad; Omar, Zoharah (Macrothink Institute, 2013)
This study surveys English language teachers’ pressure to improve students’ scores in standardized English examinations and how it has affected their classroom practices. The purpose of this study is to explore the teachers’ level of pressure to improve students’ performance in the examination. This study also seeks to investigate whether there are any differences in terms of classroom practices between teachers who express high pressure and low pressure. In this study, classroom practices are determined by four variables which are; (i) test preparation activities, (ii) mode of instruction during English lesson, (iii) instructional content, and (iv) teachers’ involvement in motivational practices. Responses were analysed using Multivariate Analysis of Variance (MANOVA) to determine whether there is any significant difference in terms of the four classroom practices variables and the pressure subgroups. This study found that teachers are pressured to improve students’ scores in standardized English examinations. Further, there are significant differences between teachers experiencing high pressure and low pressure in terms of their classroom practices, mode of instruction, instructional content and motivational practices.